Frontier Research at the Jicamarca Radio Observatory - (:unkn) unknown (My University, 2026)
The ionized portion of the upper atmosphere at the magnetic equator (equatorial ionosphere) is a unique plasma environment which hosts diverse plasma phenomena ranging from equatorial plasma bubbles to small-scale plasma structures. Plasma bubbles and oth